Effect of black carbon on sorption and desorption of phosphorus onto sediments. (September 2019) - Zhang, Hong-Hai; Cao, Xiao-Yan; Wang, He; Ma, Zhun; Li, Jing; Zhou, Li-Min; Yang, Gui-Peng
Abstract: The sorption behavior of phosphorus onto sediment was investigated with the addition of BC derived from incomplete biomass combustion (PC). The sorption kinetic curves of phosphorus onto PC and sediment could be described by a two-compartment first order equation, and the sorption isotherms fit the Freundlich model well. With increasing amounts of PC added, the sorption capacity increased while the HI did not change much. The distribution of phosphorus forms showed that CaP (ACa-P plus DAP) constituted the highest fraction in the sediment samples. Throughout the sorption process, CaP and OP changed very little, but the Ex-P and FeP increased obviously, and the presence of PC made this increase more significantly. The high specific area and the presence of iron and aluminum, as well as the modification of the sediments surface properties, make the addition of PC be favorable for the sorption of phosphorus onto sediments. Highlights: The effects of BC on the sorption character of sediment were investigated. The sorption and desorption isotherms show BC enhanced phosphorus sorption. Ex-P and FeP increased more obviously after sorption with BC added. The BC addition has little effects on CaP and OP contents. The metal residual in PC may affect the combination of sediment and phosphorus.